2022
DOI: 10.3389/fneur.2022.942956
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Headaches Due to COVID-19 Infection

Abstract: Since December 2019, the time when the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was spotted, numerous review studies have been published on COVID-19 and its neuro invasion. A growing number of studies have reported headaches as a common neurological manifestation of COVID-19. Although several hypotheses have been proposed regarding the association between headache and the coronavirus, no solid evidence has been presented for the mechanism and features of headache in COVID-19. Headache also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Over 70% of respondents reported experiencing a headache, fatigue, and myalgia, and more than 20% of respondents considered these three symptoms are severe. Previous studies have shown that headache was the second‐most common symptom after Omicron infection in the acute phase 14 . In the early stages of the Omicron variant, fatigue emerged as one of the predominant symptoms 15 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Over 70% of respondents reported experiencing a headache, fatigue, and myalgia, and more than 20% of respondents considered these three symptoms are severe. Previous studies have shown that headache was the second‐most common symptom after Omicron infection in the acute phase 14 . In the early stages of the Omicron variant, fatigue emerged as one of the predominant symptoms 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that headache was the second-most common symptom after Omicron infection in the acute phase. 14 In the early stages of the Omicron variant, fatigue emerged as one of the predominant symptoms. 15 The severity of fatigue symptoms has shown variation with the evolution of the strain.…”
Section: Discussionmentioning
confidence: 99%
“…Higher morbidity and mortality rates are seen in co-infection with bacterial and viral organisms [ 3 ]. Benign neurological symptoms, like headaches and anosmia, are commonly reported with COVID-19 [ 5 , 6 ]. Patients with more severe infections are likely to develop neurologic manifestations (40%), especially acute cerebrovascular disease [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study assessing the persistent cough in COVID-19 when the original strain was dominant showed that 20.9% of hospitalized patients had a persistent cough after three weeks [26]. The possible mechanisms of chronic headache in COVID-19 are a direct invasion of SARS-COV2 to the nerve and subsequent injury due to pro-inflammatory mediators and cytokines in the central nervous system [27]. In a multicentric study where the wild-type variant was prevalent, 19% of patients experienced headaches for up to three months [28].…”
Section: Omicron Infection Was Milder Than Deltamentioning
confidence: 99%